(untitled) (Revista Sistemas de Producción Agroecológicos, 2015)
The aim of this study was evaluate the productive performance and conduct an economic analysis of the use of antibiotic virginiamycin as additive in corn-based supplementation for grazing heifers. Were used 24 animals Brangus 260.29 ± 42.93 days aged and initial average weight of 233.9 ± 19.32 kg, individually supplemented, grazing Brachiaria hybrid CIAT 36087 (mulato II) with average availability of 7885.0 kg of dry matter per hectare. The evaluated treatments consisted of supplementation with 0.8% corn with respect to body weight (PV) (T1 = Control); 0.5% of PV corn more 0.00225% PV in virginiamycin (T2 = virginiamycin 0.5); and 0.8% of PV corn more 0.00225% PV in virginiamycin (T3 = virginiamycin, 0.8). No statistical difference (P>0.05) were observed during the experimental period for body weight (PC), body condition score (PCC), average daily gain (GDP), loin eye area (AOL), ultrasonography of the channel (subcutaneous fat thickness (EGS) and the haunch (EGA), and reproductive tract score (PRT)). The replacement of 0.3% of PV corn by virginiamycin in treating two produced the same performance and PTR productive than the other treatments, enabling lower cost of supplement heifer grazing mulato II. Although statistical differences were not presented, numerically the treatment with greater weight gain was the T3 (virginiamycin 0.8) with 390 g/day followed T2 (virginiamycin 0.5) with 290 g/day and finally T1 (only maize supplementation) with 270 g/day.